2011
DOI: 10.1117/1.3556722
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Raman spectroscopy for enhanced identification of bladder tumor cells in urine samples

Abstract: Abstract. Standard Raman spectroscopy (SRS) is a noninvasive technique that is used in the biomedical field to discriminate between normal and cancer cells. However, the presence of a strong fluorescence background detracts from the use of SRS in real-time clinical applications. Recently, we have reported a novel modulated Raman spectroscopy (MRS) technique to extract the Raman spectra from the background. In this paper, we present the first application of MRS to the identification of human urothelial cells (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 23 publications
0
69
0
Order By: Relevance
“…Thus, modulating the excitation wavelength decouples the Raman spectral features from the stationary fluorescence background. This technique has been used in Raman analysis of blood [172] and urine [173]. Canetta et al have also implemented this technique in a fiber-based probe [173].…”
Section: Fluorescence Emissionmentioning
confidence: 99%
“…Thus, modulating the excitation wavelength decouples the Raman spectral features from the stationary fluorescence background. This technique has been used in Raman analysis of blood [172] and urine [173]. Canetta et al have also implemented this technique in a fiber-based probe [173].…”
Section: Fluorescence Emissionmentioning
confidence: 99%
“…[9,32] This altered characteristics of biomolecules may also be used in the diagnosis of diseases such as diabetes, urinary tract infections, and other diseases including cancers of oral, cervix, prostate, and bladder cancer. [9,32,[38][39][40][41][42][43][44] Detailed reports were available on FS of urine for oral and cervical cancer detection. [9,32,41] Several studies have also been reported in IR and Raman spectroscopic characterization of urine for urinary tract infections and tumors of prostate and bladder.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58][59][60][61] Raman spectroscopy has been successfully employed to both in vivo and in vitro, and one can easily find its application in various fields of medicine including pathology, 62,63 physiology, 64 virology, 65 urology, 66,67 and dentistry. [68][69][70] Either by using cells, dissected tissues or real time monitoring during surgery, researchers have demonstrated the utility of Raman spectroscopy, particularly in cancers related to brain, 71,72 83,84 Additionally, by analyzing biofluids such as blood and urine, non-invasive diagnostic assays are also being actively developed for many diseases such as diabetes (glucose level monitoring), 85,86 cancer, 87,88 asthma, 89 and malaria. 90,91 Most of these studies relied on univariate analysis (one or two marker bands used for biomolecular identification).…”
Section: Medical Applicationsmentioning
confidence: 99%